Evaluation of Plasma Free Amino Acid and Carnitine Levels in Patients with Cesarean Scar Pregnancy - Tammo, Omer; Uyanikoglu, Hacer; Koyuncu, İsmail (Combinatorial Chemistry & High Throughput Screening, 2021)
Aim and Objective: This study aimed to explore the plasma free amino acid (FAA) and carnitine levels in pregnant women with cesarean scar pregnancy (CSP), and to compare them with those of healthy pregnant women. Materials and Methods: This prospective and randomized controlled study was conducted in patients admitted to Harran University Medical Faculty Hospital Obstetrics Clinic between January 2018 and January 2019. A total of 60 patients were included in the study, and the patients were divided into two groups: the CSP group (n = 30) and the healthy pregnant group as the control group (n = 30). The blood samples were taken from the participants between 7 - 12 weeks of gestation. Twenty-seven carnitines and their esters and 14 FAAs were analysed by liquid chromatography – mass spectrometry (LC-MS/MS). Results: The mean plasma concentrations of some carnitines, including C2, C5, C5-OH, C5-DC, C6, C8-1, C12, C14, C14-1, C14-2, C16, C16-1, C18, and C18-1 were significantly higher in the CSP group than in the control group. However, other carnitines, including C0, C3, C4, C4-DC, C5- 1, C6-DC, C8, C8-DC, C10, C10-1, C18-1-OH, and C18-2, were similar in both groups. The plasma levels of some FAAs, including Methyl Glutaryl, Leu, Met, Phe, Arg, Orn, and Glu values, were significantly higher in the CSP group than in the control group. However, there was no statistical significance in other FAA levels, including Val, Asa, Tyr, Asp, Ala, Cit, and Gly between the two groups. Additionally, Pearson’s correlation analysis showed that there were significantly positive correlations between many FAA and carnitine values. Conclusion: Since several plasma carnitines and FAA levels were higher in the CSP group than in the control group, we think that scar pregnancy increases the metabolic need for myometrial invasion. Also, we think that these results may be useful in clinical practice for CSP diagnosis.
Keywords: pathogenesis